Effects of Scallop Shells and Starfish (Asterias amurensis) on Stabilization of Metalloid (As) and Heavy Metal (Pb and Zn)-Contaminated Soil - Se Hyun Park; Sang Hyeop Park; Agamemnon Koutsospyros; Deok Hyun Moon (Agronomy, 2024)
Mining and industrial operations are often associated with metalloid and heavy metal contamination of terrestrial and aquatic ecosystems. Heavy metals can weaken the soil’s purification ability to remediate and can accumulate in the human body through crops grown in contaminated soil. In this study, a stabilization method was applied for the remediation of arsenic (As) and heavy metal (Pb and Zn) contaminated soil. Scallop shells (SLS) and starfish (Asterias amurensis, ASF), commonly regarded as waste resource materials, are selected as stabilizers. Proper recycling/reuse measures are required to limit uncontrolled disposal of SLS and ASF, prevent environmental degradation of coastal areas, and take advantage of their high calcium carbonate contents. The stabilizers were processed through −#10 mesh (0.2 mm) and −#20 mesh (0.85 mm) sieves. In addition, calcined stabilizers were produced by calcining SLS and ASF at 900 °C to compare stabilization efficiency based on the presence/absence of high-temperature heat treatment. Each of the three types of processed stabilizers was added to contaminated soil at 2 to 10 wt.%, and the mixtures were subjected to wet curing for 28 days. Extraction with 0.1 N HCl was applied for stabilization efficiency assessment. Crops were cultivated in the stabilized soil to evaluate As and heavy metal immobilization capacity. Analysis by X-ray diffraction (XRD) established that calcite (CaCO3) was observed in the natural materials and quicklime (CaO) in the calcined materials. The stabilization efficiency assessment results showed that treatment with SLS and ASF effectively reduced the elution of Pb and Zn. SLS was effective in immobilizing As, but the application of natural ASF increased the leachability of As due to the presence of organic matter. However, applying calcined ASF effectively immobilized As because the organic matter was removed at high temperatures. When the transition of As and heavy metals to crops was evaluated, Pb concentrations that exceeded the criterion for leafy vegetables were detected in the lettuce grown in contaminated soil. However, Pb was not detected in the lettuce grown in SLS- and ASF-treated soil, confirming the stability of heavy metal immobilization. Scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM-EDX) analysis showed that the pozzolanic reaction is related to heavy metal immobilization, and Ca–As precipitation is related to the immobilization of As. The results of this study verified that SLS and ASF effectively immobilize As and heavy metals (Pb and Zn) around mines and that they can be used safely in agricultural soil.